Views of the Qur'an's Story Against Musyarokah - Muhammad Nabil (Penerbit Hellow Pustaka, 2025)
Al-Qur'an is a revelation sent down by Allah SWT, through the angel Gabriel, and revealed gradually to the last prophet, namely Rasulullah SAW. Not least in it tells the various stories of the former, which is nothing else for us as God's creatures is to take every ibrah, and make it a role model in life. It cannot be denied that humans are social beings, which cannot be separated from human assistance in any way. One of the characteristics of humans as social beings is the running of economic life, it is inevitable that economic morals are contained in the story of the Qur'an. Examined from the economic dimension, the story of the Prophet Dawud AS which is enshrined in the Qur'an provides a lesson that it is a bad thing when someone is unfair when establishing musyarokah or cooperation in the economy.